Neoadjuvant chemotherapy response in androgen receptor-positive triple-negative breast cancer: potential predictive biomarkers and genetic alterations - Ming Li; Shuling Zhou; Hong Lv; Mengyuan Cai; Ruohong Shui; Wentao Yang (Breast Cancer Research)
Abstract Background The aim of the present study was to investigate whether the androgen receptor (AR) status affects the efficacy of neoadjuvant chemotherapy (NACT) in triple negative breast cancer (TNBC) patients, and to elucidate the predictive biomarkers and mutations associated with pathological complete response (pCR) in AR-positive TNBC patients. Methods The current retrospective cohort included 226 TNBC patients who underwent NACT. AR and FOXC1 were assessed by immunohistochemistry on pretreatment biopsy specimens of 226 TNBC patients from 2018 to 2022. The clinicopathological features of AR-negative, AR < 10%, and AR ≥ 10% TNBC patients were analyzed to confirm the appropriate threshold. The response was evaluated in terms of pCR and Miller-Payne (MP) grade in the subsequent mastectomy or breast conservation samples. Next-generation sequencing (NGS) was utilized to further investigate the molecular characteristics of 44 AR-positive TNBC patients. Results Among the 226 TNBC patients, compared with AR-negative and AR < 10% tumors (68.58%, 155/226), AR ≥ 10% TNBC patients (31.41%, 71/226) exhibited distinct clinicopathological features, while no significant difference was detected between those with AR-negative tumors and those with AR < 10% tumors. Thus, tumors with AR ≥ 10% expression were defined as having AR positive expression. The pCR rate of AR-positive TNBCs was lower than that of AR-negative TNBC patients (12.68% vs. 34.19%, p < 0.001). In TNBC, multivariate analysis demonstrated that FOXC1 was an independent predictor of pCR (p = 0.042), whereas AR was not. The pCR rate was higher in FOXC1 positive patients than in FOXC1 negative patients (34.44% vs. 3.13%, p < 0.001). In the AR-positive TNBC subgroup, patients with FOXC1 expression had lower AR expression, higher Ki-67 expression, and higher histological grade. Compared with AR-positive TNBC patients who achieved pCR, the non-pCR patients had a greater percentage of mutations in genes involved in the PI3K/AKT/mTOR pathway. Conclusions The current study indicated that the AR-positive TNBC is correlated with lower rates of pCR after NACT. The expression of FOXC1 in TNBC patients and AR-positive TNBC patients could be utilized as a predictive marker for the efficacy of NACT. The present study provides a rationale for treating these non-pCR AR-positive TNBC tumors with PI3K/AKT/mTOR inhibitors.